2021
DOI: 10.1155/2021/9033842
|View full text |Cite
|
Sign up to set email alerts
|

To Predict Anti-Inflammatory and Immunomodulatory Targets of Guizhi Decoction in Treating Asthma Based on Network Pharmacology, Molecular Docking, and Experimental Validation

Abstract: Asthma, characterized by the continuous inflammatory response caused by a variety of immune cells, is one of the most common chronic respiratory diseases worldwide. Relevant clinical trials proved that the traditional Chinese medicine formula Guizhi Decoction (GZD) had multitarget and multichannel functions, which might be an effective drug for asthma. However, the effective ingredients and mechanisms of GZD against asthma are still unclear. Therefore, network pharmacology, molecular docking, and cell experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Visualisasi reseptor dengan ligan alami maupun ligan uji menggunakan Visualisasi ligplot+ dengan menunjukkan beberapa ikatan yakni ikatan hidrofobik dan ikatan hidrogen berdasarkan interaksi residu asam aminonya 32 . Protein target 4NRE memiliki residu asam amino yang merupakan sisi katalitik yang diperlukan untuk penghambatan kinerja enzim sebagai inhibitor kompetitif yakni residu His373, His378 dan His553 yang berikatan secara hidrofobik pada konformasi bentuk U enzim 33 .…”
Section: Prediksi Bioavailabilitas Dan Toksisitas Liganunclassified
“…Visualisasi reseptor dengan ligan alami maupun ligan uji menggunakan Visualisasi ligplot+ dengan menunjukkan beberapa ikatan yakni ikatan hidrofobik dan ikatan hidrogen berdasarkan interaksi residu asam aminonya 32 . Protein target 4NRE memiliki residu asam amino yang merupakan sisi katalitik yang diperlukan untuk penghambatan kinerja enzim sebagai inhibitor kompetitif yakni residu His373, His378 dan His553 yang berikatan secara hidrofobik pada konformasi bentuk U enzim 33 .…”
Section: Prediksi Bioavailabilitas Dan Toksisitas Liganunclassified
“…Through integrated network pharmacology, many researchers have found that Danlong Dingchuan decoction can inhibit the onset of asthma by reducing inflammatory factors in the lung tissues [ 23 ]. Guizhi decoction can regulate macrophages to exert anti-inflammatory effects and participate in immune regulation to treat asthma [ 24 ]. The aforementioned findings indicate that the systematic and holistic characteristics of network pharmacology coincide with the overall regulation of multitargets and multipathways of Chinese traditional medicine formulas.…”
Section: Introductionmentioning
confidence: 99%
“…TE possesses a diverse array of biological actions, including antineuroinflammatory and antioxidative activities [ 24 , 25 ]. Glycyrrhizin (GLY), a triterpenoid saponin compound, is the main bioactive constituent of Glycyrrhiza glabra L., and has been shown to possess antineuroinflammatory and neuroprotective properties [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy has become an emerging therapeutic strategy for complex diseases, such as neurodegenerative diseases, ofering improved clinical outcomes and reduced toxicity through a multitarget approach [26][27][28][29][30]. Te fundamental treatment principle of combination therapy is synergy, where the combined efects are greater than the sum of the individual efects [31].…”
Section: Introductionmentioning
confidence: 99%